2001
DOI: 10.1038/labinvest.3780270
|View full text |Cite
|
Sign up to set email alerts
|

Human Hepatocellular Carcinoma (HCC) Cells Require Both α3β1 Integrin and Matrix Metalloproteinases Activity for Migration and Invasion

Abstract: SUMMARY:Hepatocellular carcinoma (HCC) is the most frequent malignant tumor of the liver; prognosis depends on the tendency to metastasize. Cancer cell invasion is regulated by proteolytic remodeling of extracellular matrix components and by integrin expression. We have shown that matrix metalloproteinase-2 (MMP-2) and membrane-type-1 matrix metalloproteinase (MT1-MMP) cleave Laminin-5 (Ln-5), stimulating cell migration. Here we report that all HCC cells express MT1-MMP, migrate on Ln-1 and Collagen IV, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 49 publications
10
134
1
1
Order By: Relevance
“…Furthermore, in our model, it is very likely that both the a6b4 and a3b1 integrins are involved in the Ln-5 signal pathway since both anti-a3-and anti-a6-blocking antibodies inhibit Ln-5-mediated survival in cytotoxicity experiments. Thus, consistently with our previous work (Giannelli et al, 2001), in the HCC model, it is possible that either a3b1 or a6b4 are implicated in signal transduction, mainly depending on which receptor is predominantly expressed. Therefore, these data could contribute to explain the discrepancy in the literature between the involvement of a3b1 and a6b4 in cancer aggressiveness.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, in our model, it is very likely that both the a6b4 and a3b1 integrins are involved in the Ln-5 signal pathway since both anti-a3-and anti-a6-blocking antibodies inhibit Ln-5-mediated survival in cytotoxicity experiments. Thus, consistently with our previous work (Giannelli et al, 2001), in the HCC model, it is possible that either a3b1 or a6b4 are implicated in signal transduction, mainly depending on which receptor is predominantly expressed. Therefore, these data could contribute to explain the discrepancy in the literature between the involvement of a3b1 and a6b4 in cancer aggressiveness.…”
Section: Discussionsupporting
confidence: 88%
“…However, this Ln-5 activity was completely inhibited by anti-a3 but not by anti-a6 integrin-blocking antibodies in HLF cells, and was completely inhibited by anti-a6 in Alexander cells. These results are consistent with our previous work reporting a strong expression of a3 integrin in HLF, while Alexander cells were a3 integrin negative but intensely a6 positive (Giannelli et al, 2001).…”
Section: Extracellular Matrix Proteins Modulate Gefitinib Effectivenesssupporting
confidence: 93%
See 1 more Smart Citation
“…22-25 (b) In some cells carcinogenesis is associated with a switch in integrin expression; for example, the major integrins a5b1 and a6b1 on normal hepatocytes are replaced by a1b1, a2b1 and a3b1, which are abundantly expressed in cancer cells. [26][27][28] This switch of integrin expression is associated with the acquisition of the migratory capacity, suggesting an important role for these integrins in cancer cell motility. Furthermore, several growth factors, which are abundantly expressed in the tumor microenvironment, are considered potent stimulators of the integrin expression.…”
Section: Introductionmentioning
confidence: 98%
“…Since it has been previously reported that HCCs make different matrix components from normal liver (Torbenson et al, 2002;Gulubova et al, 1997;Zhao et al, 1996;Koukoulis et al, 1995;Torimura et al, 1994;Grigioni et al, 1991;Jagirdar et al, 1985;Szendroi et al, 1985;Sell and Ruoslahti, 1982;Theret et al, 2001;Giannelli et al, 2001;Lebail et al, 1997;Kin et al, 1994;Tabarin et al, 1987), we examined the possibility that this relative resistance of HCC cell lines to prothrombin, could be attributable to an HCC matrix that was different from normal hepatocytes. We tested this idea by growing Hep3B human hepatoma cells to partial confluence and the HCC cells were then lysed in their tissue culture dishes.…”
Section: Discussionmentioning
confidence: 99%